MENGATASI TANTANGAN SEKOLAH RAMAH INKLUSI: REFLEKSI KEPALA SEKOLAH MEMBANGUN LINGKUNGAN BELAJAR SUPORTIF BAGI ABK - ANDRI WIBOWO; LIFTIAH LIFTIAH; ALI FORMEN (STKIP Subang, 2026)
This study addresses the challenges faced by an elementary school principal in creating an inclusive, supportive learning environment for children with special needs (disleksia, ADHD, and speech delay) in the absence of special assistant teachers (GPK). The purpose is to identify real challenges and practical solutions based on reflective practice. A qualitative case study approach with reflective practice was employed, involving the principal as the key informant, along with five classroom teachers, one sports teacher, one religion teacher, and seven parents. Data were collected through participatory observation, in-depth interviews, and documentation over three months. Findings reveal four main challenges: limited teacher competency in understanding the characteristics of dyslexia, ADHD, and speech delay; lack of appropriate facilities and learning media; inconsistent home-based stimulation from parents; and the absence of professional staff such as psychologists or speech therapists. In response, practical solutions were implemented: ongoing teacher training tailored to each subject (classroom, sports, religion); provision of low-cost interactive media (homemade alphabet cards, simple fidget tools, picture cards); strengthening parent collaboration through monthly meetings and daily activity sheets; and optimizing the principal’s role to collaborate with community health centers, university psychologists, and student interns. After one year, positive impacts include improved letter differentiation for dyslexic students, increased focus duration (10–15 minutes) for ADHD students, and initial two-to-three-word utterances for speech-delayed children. This study concludes that despite resource limitations, a supportive inclusive school can be achieved through collaboration among all teachers, parents, and the community.